Effect of compost and NPK on the levels of microorganisms and cadmium in soil and almond of cocoa - Florida Rofner, Nelino (2019)
Cocoa (Theobroma cacao L.) is an important crop for Peru; reports of high cadmium content (Cd2+) cause problems for the sector. However, research highlights that organic management improves the microbiological activity of the soil and the absorption of cadmium in almonds. Therefore, the effect of compost and NPK in different soil microbial groups and the available Cd in soils and cocoa beans CCN-51 was evaluated. A completely randomized block design was used, with four treatments and four repetitions, where: T1 control, T2 compost (3 000 kg. ha-1), T3 NPK (84-35-161) and T4: compost (1 500 kg. ha-1) plus NPK (42-18-80). The population of viable aerobes, actinomycetes, fungi and nitrogen fixers were evaluated using the plate count technique with serial dilutions (103). The Cd available with 0.05 M EDTA and in almonds by 4: 1 perchloric nitric acid digestion. The population of viable aerobes was 104 UFC / g, actinomycetes 104 to 105, fungi and nitrogen fixers 103 UFC/g; the Cd in the soil varies from 0.17 to 0.25 µg. g-1 and in almonds from 0.31 to 0.43 µg. g-1 No differences (p <0.05) were found between treatments and the different microbial groups, except Cd2+ in almonds. It is concluded that the compost showed potential to reduce the Cd in cocoa almonds.